From visible pasts to an invisible presence: new criminological reality after planetary cyber attack 12/05/17 Wannacry - Zhesterov, Pavel (Przegląd Wschodnioeuropejski, 2019)
The fourth industrial revolution is transforming crime and fight against it, causing fundamental consequences for research in the field of criminal law. Under the conditions of the second decade of the 21st century, the terms ‘Internet’, ‘information and telecommunications network’, ‘electronic network’, ‘communications facility’, ‘mobile communications’ are no longer an IT specialist dictionary, in the meantime they affect the doctrine of criminal repression and integrate into a scientific turnover of specialists in the field of criminal law and criminology. Transformation of crime has caused serious gaps, both in the theory of criminal law and in criminal procedural and criminal executive law inextricably bound with it. The emergence and exponential development of the Internet, electronic communications, control and tracking systems and many other technical achievements create for researchers three types of problems that need to be discussed and resolved. First, the problem of national sovereignty in criminal matters (the operation of criminal law in space) and jurisdiction, which are in contradiction in the boundless cyberspace. Secondly, the prognostic problem, which urges not only to forecast the influence of modern technologies on substantive criminal law, criminal procedure, execution of criminal punishment, but also to anticipate the general impact of technology on Russian society and the way of life of its members. Thirdly, the problem of expenses resulting from the introduction of high-tech crime prevention measures, the cost of which is constantly growing. The interdependence of these problems should form the basis of criminal law research in the era of augmented reality under the conditions of exponential growth of cyber threats directed at citizens, businesses and governments.